Vorinostat enhances the therapeutic potential of Erlotinib via MAPK in lung cancer cells - Amany I Alqosaibi; Shaimaa Abdel-Ghany; Fatma Al-Mulhim; Hussein Sabit (Cancer Treatment and Research Communications, 2022)
Background: Lung cancer is the second most common cancer in both men and women, with an estimated 235,760 new cases and 131,880 deaths in 2021 in the US. Despite the modern therapies being available such as radiotherapy and chemotherapy, death rates are still increasing. Erlotinib (ERL) is one of the treatment options for lung cancer, although the probability for the patients to develop resistance to ERL constrains its reliability. The aim of the present study is to assess the synergetic effect of combining ERL with vorinostat (SAHA) on the progression of lung cancer cells. Results: Adenocarcinoma alveolar basal epithelial cells (A549) were treated with either ERL, SAHA as mono drugs or with the combination of them for 24 h. Cytotoxicity assay and cell cycle analysis along with apoptosis detection were investigated. The expression profile of CDH1, TGF1, and MAPK was also assessed. Results showed an elevation in the apoptosis level in all treatments compared to WISH; the normal human amnion-derived cells. Furthermore, the treatments caused the cell cycle to arrest at G2/M, indicating its cytotoxic activity. Conclusion: The combination of SAHA and ERL significantly increased the level of apoptosis in lung cancer cells. Meanwhile, this combination treatment downregulated MAPK compared to the mono drugs and the control cells, suggesting the potential role of MAPK in regulating apoptosis and cell cycle machinery in lung cancer.